2021
DOI: 10.1186/s40644-021-00419-1
|View full text |Cite
|
Sign up to set email alerts
|

CT and MRI findings of cystic renal cell carcinoma: comparison with cystic collecting duct carcinoma

Abstract: Background Cystic renal cell carcinoma (CRCC) and cystic collecting duct carcinoma (CCDC) share similar oncogeni and some imaging findings. The aim of this study was to characterize the clinical and CT imagings features of CRCC and CCDC. Methods Thirty-three patients with CRCC and thirteen patients with CCDC with pathologically proven were retrospectively studied. Tumor characteristics were assessed. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Investigation of the expression of CCDC family genes in various tumors has been the subject of many studies in recent years [ 33 , 34 ]. Numerous studies have shown abnormal expression of the CCDC family genes in various tumors, including nonsmall cell lung cancer [ 35 ], liver cancer [ 11 ], renal cell carcinoma [ 36 ], gastric cancer [ 10 ], breast cancer [ 37 ], and other malignancies. However, CCDC45 has not been reported in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of the expression of CCDC family genes in various tumors has been the subject of many studies in recent years [ 33 , 34 ]. Numerous studies have shown abnormal expression of the CCDC family genes in various tumors, including nonsmall cell lung cancer [ 35 ], liver cancer [ 11 ], renal cell carcinoma [ 36 ], gastric cancer [ 10 ], breast cancer [ 37 ], and other malignancies. However, CCDC45 has not been reported in HCC.…”
Section: Discussionmentioning
confidence: 99%